Primary Schools’ Preparedness To Integrate Visually Impaired Learners Into Inclusive Education In Bomet County, Kenya - Maemba, Lynner Sophie; Maina, Anne; Ogola, Fredrick O. (My University, 2016)
Inclusive Education is an approach in which learners with special needs receive services and support appropriate to their individual needs within the regular education setting. The study sought to find out how regular public primary schools have been prepared to integrate the visually impaired learners into inclusive education in Bomet County, Kenya. The objectives of the study was to investigate the determinants of primary schools’ preparedness to integrate the visually impaired learners into inclusive education in primary schools. The research adopted descriptive survey design as this allowed description of issues as they are. Purposive sampling procedure was used to select the sample population. Questionnaires were used to obtain data from teachers, head teachers and EARC coordinators while interviews were designed for learners with V.I.C. Data was analyzed using descriptive statistics and presented in graphs, pie-charts and frequency tables for interpretation. The study was pegged on constructivist theorist of Zone of Proximal Development (ZPD) of Lev Vygotsky and Maria Montessori. The study found out that integration of inclusive education for the V.I learners faced many challenges which included; insufficient skills by teachers to teach these learners, since most of them have not undergone any training in special education, most did not have braille skills and could not teach the V.I learners effectively with the other normal learners. Major conclusions therefore were: schools should adapt the environment to suit the V.I, teachers be trained adequately to teach the V.I meaningfully, the government to give more fund to support SNE programmes in schools, more SNE personnel to be employed to supervise these programmes.